Development and Psychometric Properties of the Decision Making on the Type of Delivery Questionnaire in Iranian Women - Robab Latifnejad Roudsari; Maryam Zakerihamidi; Effat Merghati Khoei; Anoshirvan Kazemnejad (Shiraz University of Medical Sciences, 2017)
Background: A tool which can help to decide on the determinants in selecting the delivery type is an effective step towards the goals of the World Health. This study aimed to develop and evaluate the psychometric properties of a scale based on Iranian culture to make decision on the type of delivery. Methods: This is a methodological study using a questionnaire proposed by Schneider. The following steps were used to design the project. In the first step, perceptions and experiences of 45 pregnant women, postpartum women, midwives, gynecologists and non-pregnant women were determined based on interviews and observations using focused ethnography. In the second stage, the terms in the questionnaire based on qualitative study was assessed. Then, in the third stage, psychometric testing of the decision making on the type of delivery scale (DMTDS) based on the cultural concepts of decision making towards the type of delivery and its influencing factors based on focused ethnography using face validity, content validity, construct validity, internal consistency and reliability was done on400 pregnant and postpartum women. Results: The initially developed scale consisted of 60 items on a 5-point Likert scale, which reduced to 43 items following measurement of the face and content validity. The results of the exploratory factor analysis elicited 36 items and a seven-factor structure including motivational beliefs on vaginal delivery, social beliefs towards childbirth, motivational beliefs on cesarean delivery, personal beliefs, sources of information, catastrophic thinking and child birth experiences. Cronbach's alpha coefficient (0.80) confirmed the high internal consistency of the scale. Conclusion: The developed questionnaire appears to be a valid and reliable tool for health care providers to measure the women's decision making towards type of delivery. Therefore, this tool can be used in the Iranian community. The scale may help the midwives and obstetricians to be aware of the women's decision regarding their choice of delivery and as a result to plan appropriately in order to reduce unnecessary cesarean sections.